2021
DOI: 10.1007/s13202-021-01408-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and evaluation of stearyl acrylate-co-behenyl acrylate copolymer as a pour point depressant of waxy crude oil

Abstract: Pour point depressant (PPD) has the competitive advantage of lowering the temperature of the wax appearance (WAT) and crude oil viscosity. In this paper, a novel PPD of poly stearyl acrylate-co-behenyl acrylate (SA-co-BA) in various mass ratios (1:1, 2:1, 3:1, 1:2 and 1:3) was effectively synthesized by solution radical polymerization method, and characterized by fourier transform infrared FTIR, proton nuclear magnetic resonance NMR, x-ray diffraction XRD and scanning electron microscopy SEM. The SA-co-BA PPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Meanwhile, the characteristic peaks around 1.60, 1.83, and 2.14 ppm emerge, which belong to the backbone methylene and methine protons of the main‐chain repeating units of NIPAM and SA. [ 25–27 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the characteristic peaks around 1.60, 1.83, and 2.14 ppm emerge, which belong to the backbone methylene and methine protons of the main‐chain repeating units of NIPAM and SA. [ 25–27 ]…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the characteristic peaks around 1.60, 1.83, and 2.14 ppm emerge, which belong to the backbone methylene and methine protons of the main-chain repeating units of NIPAM and SA. [25][26][27] As shown in Figure 2e, X-ray diffraction (XRD) patterns indicate that both the pristine CNC film and CNC/P(NIPAM-co-SA) possess characteristic of native cellulose (semicrystalline cellulose I𝛼), while P(NIPAM-co-SA) has an extremely low degree of crystallinity. Diffraction peaks at 14.7°(101), 16.5°(101 ), 22.7°(002), and 34.1°(040) demonstrate that crystal structures of CNCs are still preserved during the whole process of swelling and polymerization.…”
Section: Bioinspired Design Of Dual-responsive Schemochrome Hydrogelsmentioning
confidence: 99%
“…It is clearly observed that the efficiency of the pour point depressant gradually enhanced with the increase in the concentration of the polymeric additives in the base oils. However, the enhancement in the pour points temperature values is because of the disruption of the rigid network of wax crystals in the base oils 5 .…”
Section: Figure 5 Effect Of Polymeric Additives Concentration On Visc...mentioning
confidence: 99%
“…For example, polymeric additives are the most important materials used as base oil additives [5][6][7][8] . In this field, there are many types of research have been achieved so far.…”
Section: Introductionmentioning
confidence: 99%
“…The Cold Finger experiment was performed at the Chemical Services and Development Center, EPRI, Cairo, Egypt to evaluate the impact of PSV copolymer and Nano-SiO 2 /PSV nano-composite as PIs. This model is used as a convenient way to simulate the wax precipitation process inside the oil pipeline according to the method described in previous studies [37,56]. After the mentioned method completion, the residual deposition of wax was gradually removed from the cold finger and measured.…”
Section: Nano-sio 2 /Psv Evaluation As a Nano-pi For Tut-waxy Crude Oilmentioning
confidence: 99%